2019
DOI: 10.1007/s42765-019-00006-x
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance 3-D Fiber Network Composite Electrolyte Enabled with Li-Ion Conducting Nanofibers and Amorphous PEO-Based Cross-Linked Polymer for Ambient All-Solid-State Lithium-Metal Batteries

Abstract: Solid electrolytes have gained attention recently for the development of next-generation Li-ion batteries since they can fundamentally improve the battery stability and safety. Among various types of solid electrolytes, composite solid electrolytes (CSEs) exhibit both high ionic conductivity and excellent interfacial contact with the electrodes. Incorporating active nanofibers into the polymer matrix demonstrates an effective method to fabricate CSEs. However, current CSEs based on traditional poly(ethylene ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…Cross‐linking results in a substantial change in not only the conductivity but also the dendrite growth suppression. For example, Yan et al have reported a new amorphous cross‐linked polymer based on the PEO matrix, the cross‐linked polymer displayed ionic conductivity of 2.40 × 10 −4 S cm −1 at room temperature, as well as good thermal stability and high solvation power 120 . But the practical use of batteries is still limited by their poor mechanical properties and low conductivity at room temperatures 121 …”
Section: Polymer Electrolytesmentioning
confidence: 99%
“…Cross‐linking results in a substantial change in not only the conductivity but also the dendrite growth suppression. For example, Yan et al have reported a new amorphous cross‐linked polymer based on the PEO matrix, the cross‐linked polymer displayed ionic conductivity of 2.40 × 10 −4 S cm −1 at room temperature, as well as good thermal stability and high solvation power 120 . But the practical use of batteries is still limited by their poor mechanical properties and low conductivity at room temperatures 121 …”
Section: Polymer Electrolytesmentioning
confidence: 99%
“…[ 1–10 ] Solid‐state rechargeable batteries have received significant attention not only because they can address conventional liquid electrolytes’ safety issues, which suffer from flammability and leakage due to organic solvents, but also the potential to enhance the overall energy density. [ 11–15 ] Among various solid‐state electrolytes (SSEs), many efforts have been devoted to solid polymer electrolytes (SPEs), which possess numerous attractive properties, including high flexibility, processability, and shape versatility, as well as low density. [ 16–26 ] These unique properties may enable them to meet large‐scale electronic devices’ requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive and sustainable power supply is always the dilemma of epidermal electronics toward prolonged operation. Batteries offer the promising options, but they are still severely hindered by the weight/size and periodic recharging demands [ 26 28 ]. Ideally, the human body provides a wealth of potential energy sources: kinetic energy (such as body activities and muscle stretching), feeble vibrational energy (such as heartbeat, acoustic and pulse vibrations), hydraulic energy (such as human biofluids and blood flow) and chemical energy (such as glucose) [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%